A procedure for dual simple t-cannulation in the small intestine of pigs using a single right flank laparotomy - A.L. Petry; S.A. Gould; J.F. Patience (Journal of Applied Animal Nutrition)
Singular cannulation in the small intestine of pigs is a common methodology for studying nutrient digestibility, delivering compounds into the gastrointestinal tract, or repeated tissue and digesta sampling. In that respect, it is an important tool for nutritionists and researchers. However, there is a dearth of detailed methodologies describing multiple intestinal cannulations using modern techniques. The objective of this experiment was to develop a single right flank laparotomy technique that allowed for imsertion of multiple cannulas in the small intestine, with minimal variation, and allowed for externalisation of both cannulas on the same lateral side as the laparotomy. Thirty gilts (L337 × Camborough) with an initial body weight of 30.2±0.78 kg underwent the procedure. Each gilt was equipped with a simple t-cannula in the terminal ileum, approximately 10 cm cranial to the ileocecal valve, and a second t-cannula in the jejunum 240 cm distal from where the duodenum is visually posterior to the transverse colon. The procedure used hallmarks of commonly implemented terminal ileal cannulation techniques, but modified the laparotomy location and cannula externalisation sites and used a novel approach for determining the more proximal cannula location to mitigate the need of a second laparotomy. Gilts were allowed to recover for a minimum of 7 d and were used for an average of 67 days in subsequent experimental trials. Cannula longevity was from 30 to 73 kg of body weight. Pigs were necropsied for surgical site gross examination and small intestine measurements at the end of the experiment. The jejunal cannula had a mean placement of 298.90±9.96 cm distal to the pyloric sphincter with a coefficient of variation of 3.33%. Hence, this procedure provided a single laparotomy technique for obtaining digesta from multiple locations of the small intestine, with minimal variation in proximal cannula placement.